Sky-earth, lake-sea: climate and water in Maya history and landscape. (April 2016) - Luzzadder-Beach, Sheryl; Beach, Timothy; Hutson, Scott; Krause, Samantha
Abstract: Abstract : In recent years, a growing body of research has focused on the importance of water management for ancient Maya societies, and more generally on the cultural and economic significance of water as a resource. But how did this change across the centuries as cycles of drought and sea level rise, together with the growing Maya footprint on the landscape, presented new challenges? As the resolution of climatic records improves, the authors can begin to show in detail how Maya water management responded and adapted to such shifts. This included the manipulation ofaguadas and the development of wetland field systems, in the process transforming large areas of the Maya landscape.